2014
DOI: 10.1016/j.bjid.2013.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistant Staphylococcus aureus nasal carriage in neonates and children attending a pediatric outpatient clinics in Brazil

Abstract: Despite the high antibiotic pressure in our area, and the cross transmission of the healthcare-associated methicillin-resistant S. aureus clones between neonatal intensive care units and outpatients, the prevalence of methicillin-resistant S. aureus carriage is still low in our setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
9
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
5
9
3
Order By: Relevance
“…Moreover, CoNS have been the major reservoirs of resistant genes and their ability to transfer them to S. aureus may influence therapy for patients as vulnerable as neonates. Unlike Ternes et al, who reported SCCmec types I, II, and III as prevalent among nasal CoNS isolates [24], we detect the type V among the CoNS isolates, demonstrating a striking difference for the SCCmec carriage between regions of the same country. Furthermore, 91.7% of our methicillinresistant isolates were non-typeable, reinforcing that CoNS isolates present high variability in their SCCmec structure conformation.…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…Moreover, CoNS have been the major reservoirs of resistant genes and their ability to transfer them to S. aureus may influence therapy for patients as vulnerable as neonates. Unlike Ternes et al, who reported SCCmec types I, II, and III as prevalent among nasal CoNS isolates [24], we detect the type V among the CoNS isolates, demonstrating a striking difference for the SCCmec carriage between regions of the same country. Furthermore, 91.7% of our methicillinresistant isolates were non-typeable, reinforcing that CoNS isolates present high variability in their SCCmec structure conformation.…”
Section: Discussioncontrasting
confidence: 97%
“…Among 98 neonates colonized 77.6% had at least one methicillin-resistant Staphylococcus species. Despite the low prevalence of MRSA isolates in our study (2%), similar to that observed by other authors [11,24], the majority of the S. aureus isolates (55.6%) harbored pvl genes. Such a high frequency was previously reported by us, however in a study with pediatric outpatients [25].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…According to the authors, replacement of clonal groups over time might be explained by microevolution of the pathogen or by competition to adapt to the hospital environment. Furthermore, the report of the presence of the pediatric clone in central Brazil suggests that this clone is settling in Brazilian hospitals and spreading in the community, increasing the likelihood of expanding its reservoir [31]. …”
Section: Discussionmentioning
confidence: 99%